2019
DOI: 10.3390/app9050864
|View full text |Cite
|
Sign up to set email alerts
|

Selective Laser Sintering Fabricated Thermoplastic Polyurethane/Graphene Cellular Structures with Tailorable Properties and High Strain Sensitivity

Abstract: Electrically conductive and flexible thermoplastic polyurethane/graphene (TPU/GE) porous structures were successfully fabricated by selective laser sintering (SLS) technique starting from graphene (GE)-wrapped thermoplastic polyurethane (TPU) powders. Several 3D mathematically defined architectures, with porosities from 20% to 80%, were designed by using triply periodic minimal surfaces (TMPS) equations corresponding to Schwarz (S), Diamond (D), and Gyroid (G) unit cells. The resulting three-dimensional porous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 47 publications
3
57
0
Order By: Relevance
“…Glass bead/PA12 [161a] Cu/PA12 [200] CF/PA12 [201] GF/PA12 [202] Carbon black/PA12 [203] OMMT/PP [140] GNP a) /PEEK [190b] • MWCNT/PA12 [189,191,204] MWCNT/TPU [190a,204a] SWCNT b) /TPU [205] Carbon black/PA12 [206] Graphene/TPU [192] OMMT/PP [140] GNP/PEEK [190b] GNP/PA12 [207] • Low cost • Moderate filler dispersion on powder particle surfaces • Good interfacial interaction possible • Solvent intensive Melt blending and mechanical grinding CNF/PA12 [194] OMMT/PP [140] BaTiO 3 /PA11 [162] • Good filler dispersion in powder particles • Good interfacial interaction possible • Irregular particle shape • Poor powder flowability • Particle rounding or other post-processing treatment required…”
Section: Dry Mixingmentioning
confidence: 99%
“…Glass bead/PA12 [161a] Cu/PA12 [200] CF/PA12 [201] GF/PA12 [202] Carbon black/PA12 [203] OMMT/PP [140] GNP a) /PEEK [190b] • MWCNT/PA12 [189,191,204] MWCNT/TPU [190a,204a] SWCNT b) /TPU [205] Carbon black/PA12 [206] Graphene/TPU [192] OMMT/PP [140] GNP/PEEK [190b] GNP/PA12 [207] • Low cost • Moderate filler dispersion on powder particle surfaces • Good interfacial interaction possible • Solvent intensive Melt blending and mechanical grinding CNF/PA12 [194] OMMT/PP [140] BaTiO 3 /PA11 [162] • Good filler dispersion in powder particles • Good interfacial interaction possible • Irregular particle shape • Poor powder flowability • Particle rounding or other post-processing treatment required…”
Section: Dry Mixingmentioning
confidence: 99%
“…All porous structures exhibited a robust negative piezoresistive behavior, with outstanding strain sensitivity. However, the obtained results showed that GE particles obstruct the polymer powder coalescence, thereby resulting in a porous structure that exhibits an imperfect percolative network and poor mechanical properties [27]. The analysis of the literature confirms that elastomer-based porous structures realized by SLS technology with powders modified with carbonaceous fillers have been exhaustively investigated as innovative materials for piezoresistive sensors.…”
Section: Introductionmentioning
confidence: 60%
“…The thermogravimetric curves of TPU-based samples are compared in Figure 3. TPU degradation occurs in two steps as already described in our previous research [27]. Briefly, the first degradation that starts at about 280 °C is attributed to the cleavage of urethane bonds of TPU [42] and shows a maximum rate at 309 °C, accounting for about 30% mass loss.…”
Section: Thermal Propertiesmentioning
confidence: 71%
See 1 more Smart Citation
“…Hence, the use of permeability measurement devices [35][36][37][38][39] permits indirect determination of wick permeability by measuring the pressure loss (∆P) and flow rate through the medium. The flow at pore scale must be in the Darcy's regime, which means that the Reynolds number (Re) must be Re < 10 [40].…”
Section: Permeabilitymentioning
confidence: 99%